Corporate Attributes and Risk Management Disclosure of Listed Insurance Companies in Nigeria - Akpan, Dorathy Christopher; Odokwo, Rose Augustine; Akinninyi, Patrick Edet (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
Disclosure of risk management practices by firms enhances transparency, thus giving shareholders’ more confidence and lowering their uncertainty about future cash flows. This study therefore examined the effects of corporate attributes on risk management disclosures of listed insurance firms in Nigeria from 2013 to 2022. Firm size, firm profitability and firm leverage were the measures of corporate attributes employed in this study while risk management disclosure was the dependent variable. The research design adopted for this study was ex post facto and twenty-three listed insurance firms constituted the population of the study. Purposive sampling technique was employed to select eight listed insurance firms and secondary used were analysed using marginal logistic regression. The statistical package employed was STATA 16. From the analysis, it was found out that firm size, firm profitability and firm leverage have significant effect on risk management disclosure of listed insurance firms in Nigeria. Thus, it was concluded that some firm specific attributes can enhance risk management disclosures of listed insurance firms in Nigeria. Based on these findings, the study recommended that the management of insurance firms in Nigeria should strive to increase their level of profitability as more profitable firms have the incentives to engage in risk management and disclosure practices.
Keywords: Corporate Attributes; Firm Size; Leverage; Profitability; Risk Management